2012
DOI: 10.1186/1475-2875-11-298
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in histidine rich proteins among Indian Plasmodium falciparum population: possible cause of variable sensitivity of malaria rapid diagnostic tests

Abstract: BackgroundRapid diagnostic tests (RDTs) have revolutionized the diagnosis of malaria. Among the various factors affecting RDTs sensitivity is genetic variation of the antigen used. The genetic variation in PfHRP2 and PfHRP3 proteins was studied among the Indian Plasmodium falciparum isolates.MethodsOne hundred and forty isolates of P. falciparum were collected from six geographical regions of India. Target genes encoding PfHRP2 and PfHRP3 antigens were sequenced to study genetic polymorphism. Minimum detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 18 publications
10
65
0
1
Order By: Relevance
“…Genetic diversity may be particularly important for PfHRP2-based RDTs, since most of the RDTs are based on this antigen (Mouatcho and Goldring, 2013). Studies to date have documented extensive size variations between parasite strains and a high degree of genetic diversity within this antigen (Baker et al, 2010b; Baker et al, 2005; Deme et al, 2014; Kumar et al, 2012; Lee et al, 2006; Rock et al, 1987). An extreme situation is that certain parasite isolates even harbor a deletion of the pfhrp2 gene, leading to false negative results in diagnosis with PfHRP2-based RDTs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic diversity may be particularly important for PfHRP2-based RDTs, since most of the RDTs are based on this antigen (Mouatcho and Goldring, 2013). Studies to date have documented extensive size variations between parasite strains and a high degree of genetic diversity within this antigen (Baker et al, 2010b; Baker et al, 2005; Deme et al, 2014; Kumar et al, 2012; Lee et al, 2006; Rock et al, 1987). An extreme situation is that certain parasite isolates even harbor a deletion of the pfhrp2 gene, leading to false negative results in diagnosis with PfHRP2-based RDTs.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, pfhrp2 deletion-associated poor performance of RDTs has been reported in many malaria-endemic regions (Cheng et al, 2014; Koita et al, 2012; Maltha et al, 2012; Pava et al, 2010; Wurtz et al, 2013). To date, unequivocal evidence for pfhrp2 and pfhrp3 gene deletions in P. falciparum isolates has been obtained in Peru (Gamboa et al, 2010; Maltha et al, 2012), Brazil (Houze et al, 2011), Senegal (Wurtz et al, 2013), and India (Kumar et al, 2012). Apart from gene deletion, PfHRP2 sequences in different regions showed differences in the number of amino acid repeats and even some rare amino acid variants (Baker et al, 2010b; Baker et al, 2005; Deme et al, 2014; Kumar et al, 2012; Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the available RDTs are known to have certain deficiencies, such as the fact that HRP-2 is only expressed in P. falciparum and persists even after parasite clearance, thus causing false positive results [20]. The genetic variation of HRP-2 in different geographical regions has also been reported, a problem that affects the sensitivity of tests in the field [21, 22], and a large proportion of field isolates in the Peruvian Amazon lack this antigen [23]. On the other hand, pLDH-based tests were less efficient in detecting low parasite densities and yielded variable results in different studies [24], while aldolase targeting tests have been shown to lack sensitivity in recent comparative studies, possibly due to the low concentration of this antigen in the parasite [24].…”
Section: Resultsmentioning
confidence: 99%
“…The development of alternative diagnostic method like rapid diagnostic test, (RDTs) has made it possible to provide rapid and accurate detection of malaria parasites in remote areas where microscopy facility is not available. Several factors affect the performance of malaria RDTs which include test factors & parasite factors but genetic variability [12,13] and genetic deletion of these diagnostic antigens have been also questioned their sensitivity & reliability [14]. So, there is also an urgent need Volume 3 Issue 2 -2016 to develop new reliable diagnostic target of malaria parasite.…”
Section: Nuclear Peroxiredoxin As a Target For Rapid Diagnosis Of Mamentioning
confidence: 99%